The effects of environmental resource and security on aggressive behavior. Issue 3 (11th November 2016) - Ng, Henry Kin Shing; Chow, Tak Sang
Abstract : Exposure to different environments has been reported to change aggressive behavior, but previous research did not consider the underlying elements that caused such an effect. Based on previous work on environmental perception, we examined the role of environmental resource and security in altering aggression level. In three experiments, participants were exposed to environments that varied in resource (High vs. Low) and security (High vs. Low) levels, after which aggression was measured. The environments were presented through visual priming (Experiments 1–2) and a first‐person gameplay (Experiment 3). We observed a consistent resource‐security interaction effect on aggression, operationalized as the level of noise blast (Experiment 1) and number of unpleasant pictures (Experiments 2–3) delivered to strangers by the participants. High resource levels associated with higher aggression in insecure conditions, but lower aggression in secure conditions. The findings suggest that the adaptive value of aggression varies under different environmental constraints. Implications are discussed in terms of the effects of adverse environments on aggression, and the nature's effects on social behavior. Aggr. Behav. 43:304–314, 2017. © 2016 Wiley Periodicals, Inc.